2013
DOI: 10.5902/1980509810551
|View full text |Cite
|
Sign up to set email alerts
|

Substratos de origem orgânica para produção de mudas de teca (<i>Tectona grandis</i> Linn. F.)

Abstract: RESUMOA utilização de resíduos renováveis como fonte de nutrientes para produção de mudas florestais pode ser uma solução para problemas ambientais, principalmente relacionados à destinação destes materiais. Neste contexto, este trabalho teve por objetivo avaliar a utilização de substratos renováveis como componentes de substrato na produção de mudas de teca. As mudas foram produzidas em tubetes com capacidade volumétrica de 280 cm³, utilizando-se para a composição dos tratamentos esterco bovino, cama de frang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
38

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 0 publications
1
15
0
38
Order By: Relevance
“…A produção de mudas de espécies florestais constitui uma das etapas mais importantes do sistema produtivo, contudo, altamente dependente de insumos. Nesta etapa, o substrato destaca-se em importância devido à influência direta na emergência, enraizamento, retenção de água, nutrição e qualidade das mudas (Sousa et al, 2013;Trazzi et al, 2013;Lustosa Filho et al, 2015).…”
Section: Introductionunclassified
“…A produção de mudas de espécies florestais constitui uma das etapas mais importantes do sistema produtivo, contudo, altamente dependente de insumos. Nesta etapa, o substrato destaca-se em importância devido à influência direta na emergência, enraizamento, retenção de água, nutrição e qualidade das mudas (Sousa et al, 2013;Trazzi et al, 2013;Lustosa Filho et al, 2015).…”
Section: Introductionunclassified
“…The highest shoot dry matter production was observed at the ratios of 37% of poultry litter added to the commercial substrate, and 43% of poultry litter mixed with peat ( Figure 1C). Trazzi et al (2013) found the highest average of shoot dry matter in teak seedlings (Tectona grandis Linn), in the treatment consisting of 25% of commercial substrate, 40% of subsoil soil and 35% of poultry litter. The authors report that the dry matter increase with the addition of poultry litter may be related to the greater availability of nutrients and the adequate retention of water and aeration 4/10 Silva RF, Grolli AL, Welter PD, Ros CO, Scheid DL Floresta e Ambiente 2019; 26(3): e20170080 that the poultry litter provides when mixed with the commercial substrate.…”
Section: Resultsmentioning
confidence: 97%
“…Poultry litter is an abundant organic waste because of the expansion of confined poultry production, which represents the optimal source of nutrients for plants, mainly nitrogen, phosphorus and potassium, and provides good physical properties for the substrate as well (Luz et al, 2009). Trazzi et al (2013), while working with organic substrates, observed that the addition of 35% of poultry litter to the substrate presented a higher nutrient content in Tectona grandis seedlings. In a work using poultry litter mixed in the substrate, Torres et al (2011) obtained a decreasing regression in the development of physic nut seedlings, with an increase in the development of the seedlings using 10% of poultry litter and a decrease as the proportion of the organic fertilizer increased.…”
Section: Introductionmentioning
confidence: 99%
“…Resultados que também são semelhantes aos obtidos por TRAZZI et al (2013), na avaliação de substratos orgânicos destinados a produção de mudas de teca (Tectona grandis Linn. F.), onde os autores observaram que plântulas de teca dispostas em substratos compostos por maiores percentuais de esterco bovino apresentaram aumentos no comprimento da parte aérea e na fitomassa seca total.…”
Section: Resultsunclassified